The Effect of Gelatin and Propylene Glycol on the Penetration Rate of Asiaticoside from Centella asiatica (L.) Urb Leaf Extract Gel - Dahlizar, Sabrina; Anggraeni, Yuni; Munfarikhatin, Atina; Suryani, Nelly; Betha, Ofa Suzanti; Zilhadia, Zilhadia; Fajriah, Sofa; Septama, Abdi Wira; Handayani, Maulina; Herdini, Herdini (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2025)
Centella asiatica (L.) Urb. is a plant known for its potential in scar treatment due to the presence of asiaticoside, a compound capable of promoting skin cell tissue repair. However, the large molecular size of asiaticoside hinders its penetration through the skin. This study aims to evaluate the effect of gelatin and propylene glycol on the transdermal penetration of asiaticoside from a gel formulation containing Centella asiatica leaf extract. Four different formulations were tested: a control (F1, without gelatin or propylene glycol); one with 15% propylene glycol (F2); one with 4% gelatin (F3); and one with 4% gelatin and 15% propylene glycol (F4). The physical characteristics of the formulations were assessed using several parameters: organoleptic properties, pH, homogeneity, centrifugation, spreadability, viscosity, and rheological behaviour. Penetration studies were performed using a Franz Diffusion Cell with a Whatman No. 1 membrane (pre-coated with Spangler solution) for 360 minutes. The penetration data were analyzed using Liquid Chromatography–Tandem Mass Spectrometry (LC–MS/MS) with a C18 BEH column (2.1 × 50 mm; 1.8 μm particle size). The results showed that each formulation exhibited distinct characteristics. The study findings indicated that both gelatin and propylene glycol, as well as their combination, significantly influenced the penetration of asiaticoside in the gel formulation. Propylene glycol, functioning as a penetration enhancer, was found to increase the penetration of asiaticoside in both gelatin-based and liquid formulations.